Visual Field Plots: A Comparison Study Between Standard Automated Perimetry and Eye Movement Perimetry. Issue 5 (27th May 2020) - Mazumdar, Deepmala; Pel, Johan J.M.; Kadavath Meethal, Najiya S.; Asokan, Rashima; Panday, Manish; Steen, Johannes v.d.; George, Ronnie
Abstract : Supplemental Digital Content is available in the text. Abstract : Précis: This eye movement perimetry (EMP) study describes the development of saccadic reaction time (SRT)-based visual field plots, which could effectively display the presence, location, and extent of glaucomatous defects and support clinical decision-making. Purpose: EMP is capable of discriminating normal from glaucomatous visual field defects on the basis of average delays in SRTs. To classify the presence and extent of age-corrected visual field defects, it is required to create SRT-based probability maps. Aim: The aim of this study was to create visual field probability plots based on SRTs and to evaluate their clinical applicability by 2 glaucoma specialists. Materials and Methods: The development phase included 95 controls segregated into 5 age-bins to estimate normative limits of SRT. Next, for the testing phase, a set of 28 healthy subjects and 24 glaucoma patients were recruited who underwent standard automated perimetry (SAP) and EMP visual field testing. Fifty-two SAP and EMP plots were presented to 2 glaucoma specialists to classify them as normal or abnormal and to identify the defect location and pattern as 1 or more of 7 predefined categories. Results: The glaucoma specialists showed a sensitivity of 100% and a specificity of 93% and 96% for identifying normal versus abnormal visual field. For specialists 1 and 2, 85% and 92%, respectively, of EMP reports were assigned to the same category as SAP. The reports that did not agree with SAP were graded to a higher defect pattern. The intermethod agreement for specialists 1 and 2 was κ 0.92 and 0.96, respectively. Conclusion: SRT-based visual field probability plots provided a comprehensive summary of an individual's visual field status and showed comparable clinical applicability to that of SAP plots.